African origin of the malaria parasite Plasmodium vivax - (:unkn) unknown (My University, 2014)
Plasmodium vivax is the leading cause of human malaria in Asia and Latin America but is absent from most of central Africa due to the near fixation of a mutation that inhibits the expression of its receptor, the Duffy antigen, on human erythrocytes. The emergence of this protective allele is not understood because P. vivax is believed to have originated in Asia. Here we show, using a noninvasive approach, that wild chimpanzees and gorillas throughout central Africa are endemically infected with parasites that are closely related to human P. vivax. Sequence analyses reveal that ape parasites lack host specificity and are much more diverse than human parasites, which form a monophyletic lineage within the ape parasite radiation. These findings indicate that human P. vivax is of African origin and likely selected for the Duffy-negative mutation. All extant human P. vivax parasites are derived from a single ancestor that escaped out of Africa.
Keywords: African Research